Evaluating the experiment of e-learning from postgraduate students’ view at Diyala University: Case Study - Kadhim, Alaa Jawad (Al-Adab Journal, 2021)
The research aims to evaluate the experiment of e-learning from post-graduate students’ viewpoint at Diyala University. A qualitative research method was used to collect and analyse data via the SPSS program. The researcher selected the sample that consists 379 of 613 the total of the population study from different variety departments in Diyala University. An electronic questionnaire form consisted of 29 open-ended questions sent to the postgraduate students to evaluate the experiment of e-learning in Diyala University. Statistical tools were used like, T-test, Cronbach’s alpha and Tow Way ANOVA to analyse the data. The findings indicated that, evaluating the experiment of e-learning from post-graduate learners in Diyala University, a slightly below the standard at a significant level of 0.052, as a result of financial and humans’ factors – and there is a statistically significant difference between Mean score in gender variable (M=males < females). It is recommended the necessity of completing the infrastructure for the digital transforming in university education – and continue with the intense training on the use of ICT applications in learning and teaching. It is suggested to study other variables.